One flew over the cuckoo's nest [videorecording (DVD)] - Nicholson, Jack; Fletcher, Louise; Redfield, William, 1927-1976; Crothers, Scat Man; DeVito, Danny; Lloyd, Christopher, 1938-; Sampson, Will, 1933-1987; Dourif, Brad, 1950-; Kesey, Ken (Warner Bros. Entertainment, 2011)
A rebellious patient battles the nurse, and the mental institution he has been sent to.